Value Added Tax Refund Analysis - Herry Aprilia Manubulu (Jurnal Mantik, 2022)
The study aims to comprehend the process of restitution paid more tax on the value added tax at PT Tunas Baru Abadi Kupang and PT Rotendo Permai by implementing the process of tax documents. The study is a comparative descriptive study, in which it describes the comparative process of restitution over taxes for both companies' increased value increases. The data sources used in this study are the primary and secondary data collection techniques that include documentation and interviews. Research shows PT Rotendo Permai in implementing restitution there was neither a correction nor a finding at the time of inspection of the tax document by the inspection team of KPP Pratama Kupang. The reduction of restitution pays more than the 2018 value-added tax received in accordance with the one submitted on a December tax.